ART THERAPY AND AUTISM - HAQUE, SERAJ; HAQUE, MAINUL (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Autism is a developmental condition that affects social interaction and behavior in human beings. The condition falls under a wider group known autism spectrum disorder (ASD). There are some diagnostic criteria in DSM-5 for ASD [1]; the pathognomonic symptoms of the disease revolve around impairment in social communication, and behaviors that are restrictive or repetitive in nature. Psychiatrist Lorna Wing proposed a central triad of symptoms, which can be seen in Fig. 1 [2,3]. It should be noted that social imagination refers to an autistic person's inability to predict and understand the behaviors of people around them, rather than a lack of imagination as a whole. The condition can be present from birth or develop due to environmental factors or other medical causes. Elements such as genetics, as well as psychological and neurological development, may also play a key role in the condition [4]. Although there is no cure for ASD, there are some strategies that can be used to help aid an individual with autism to grow and achieve the most out of their lives. One of these approaches is the use of art therapy.